Pemberdayaan Ekonomi Ibu Rumah Tangga di Desa Sidorejo, Bengkulu Tengah Melalui Jaringan Perempuan Usaha Kecil: Pemberdayaan Ekonomi Ibu Rumah Tangga di Desa Sidorejo, Bengkulu Tengah Melalui Jaringan Perempuan Usaha Kecil - Hajar Gelis Pramudyasmono (UNIB Press, 2024)
Since the number of poor households in Indonesia is still high, the Indonesian government encourages women from these families to do small businesses by joining a network called Jar-PUK stands for Jaringan Perempuan Usaha Kecil or Small Business Women Network. This network is intended to empower women’s economy, thereby reducing poverty. Several previous studies showed that the effectiveness of Jar-PUK in empowering women’s economy is still questionable. Therefore, this study aims to examine the role of Jar-PUK in Sidorejo, a rural village in Bengkulu, Indonesia, in empowering the economy of its members. This study focused on two groups of Jar-PUK, namely Jar-PUK Seroja and Jar-PUK Sedap Malam, each consisting of 20 women. The participants of this study were selected based on purposive sampling techniques, including coordinators and members from Jar-PUK groups. Data were collected using triangulation techniques involving observation, in-depth interviews, and focus group discussions. The collected data were analyzed using a descriptive qualitative approach. The result shows that Jar-PUK has yet to become an agent of economic empowerment for its members. This study suggests that small business activities run by Jar-PUK members still need to develop to their maximum potential. The obstacles the Jar-PUK members face in running their businesses are a need for knowledge and entrepreneurship skills. These challenges hindered the optimal growth and success of their small businesses. Therefore, the Jar-PUK members need training on entrepreneur skills and mentoring to foster economic empowerment and improve their business’s overall performance.